Tuberculosis Immune Reconstitution Inflammatory Syndrome in Children Initiating Antiretroviral Therapy for HIV Infection: A Systematic Literature Review - Link-Gelles, Ruth (2014)
BACKGROUND: People with HIV initiating combination antiretroviral therapy are at risk for tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS). While this syndrome has been well researched in adults, little is known about the incidence, case fatality, underlying immunopathology and treatment approaches in children. METHODS: Major databases were searched for articles related to TB-IRIS in children. Data were abstracted using standardized forms. RESULTS: Thirteen studies were identified: 6 retrospective and 2 prospective cohort studies, 1 cross-sectional study, 3 case reports and 1 case series. In total, 303 cases of TB-IRIS were described, of which 270 were unmasking TB-IRIS, 12 paradoxical TB-IRIS and 21 were not classifiable due to lack of key information. None of the cohort studies had investigation of TB-IRIS as its primary aim. Nine studies were from Africa, 3 from Asia and 1 from Latin America. Age at cART initiation (reported by 12 studies) ranged from 1 month to 16 years. Median time from start of cART to IRIS diagnosis (reported by 8 studies) ranged from 8 days to 16 weeks. Few deaths attributable to TB-IRIS were recorded. Treatment was only discussed in 2 case studies, both of which reported children receiving corticosteroids. No studies evaluated risk factors for, or immunopathogenesis of, pediatric TB-IRIS. CONCLUSIONS: There is a paucity of information available on TB-IRIS in children. Future research assessing incidence, risk factors, case fatality and optimal treatment or prevention strategies of TB-IRIS is needed.